Symbolic Interaction of The Deaf Students in Public School - Pranata, Eka Wijaya; Latif, Mochamad Chaerul; Fanani, Fajriannoor (Jurnal The Messenger, 2019)
This study aims to know how symbolic interaction process happens to the deaf students who study in SD Maranatha 01 public school. Communication built by the deaf students to the teachers and other students who have good hearing will influence the changing of meaning and behavior. That's why the author is interested to analyze the symbolic interaction of the deaf students in public school, how the role of the teachers and other students in dealing with the deaf students to take their action and to adapt themselves in public school. The research method used in this study is descriptive qualitative conducted using observation, and interview techniques. The foundation used in this study is the theory of Symbolic Interactionism of George Herbert Mead. The conclusion of this research is; the behavior and symbolic formation happening to the deaf students of SD Maranatha 01 are influenced by the social process.